KRASG12C‐inhibitor‐based combination therapies for pancreatic cancer: insights from drug screening - Constanza Tapia Contreras; Jonas Dominik Falke; Dana‐Magdalena Seifert; Carolin Schneider; Lukas Krauß; Xin Fang; Denise Müller; Engin Demirdizen; Melanie Spitzner; Tiago De Oliveira; Christian Schneeweis; Jochen Gaedcke; et al. (Molecular Oncology)
Pancreatic ductal adenocarcinoma (PDAC) has limited treatment options, emphasizing the urgent need for effective therapies. The predominant driver in PDAC is mutated KRAS proto‐oncogene, KRA, present in 90% of patients. The emergence of direct KRAS inhibitors presents a promising avenue for treatment, particularly those targeting the KRASG12C mutated allele, which show encouraging results in clinical trials. However, the development of resistance necessitates exploring potent combination therapies. Our objective was to identify effective KRASG12C‐inhibitor combination therapies through unbiased drug screening. Results revealed synergistic effects with son of sevenless homolog 1 (SOS1) inhibitors, tyrosine‐protein phosphatase non‐receptor type 11 (PTPN11)/Src homology region 2 domain‐containing phosphatase‐2 (SHP2) inhibitors, and broad‐spectrum multi‐kinase inhibitors. Validation in a novel and unique KRASG12C‐mutated patient‐derived organoid model confirmed the described hits from the screening experiment. Our findings propose strategies to enhance KRASG12C‐inhibitor efficacy, guiding clinical trial design and molecular tumor boards.